ANALISIS PENGARUH PEMOTONGAN TRAYEK TITIK DIDIH MINYAK SOLAR TERHADAP NILAI CALCULATED CETANE INDEX (CCI) - Yusran Hedar (Jurnal Nasional Pengelolaan Energi MigasZoom, 2022)
The ignition quality of diesel fuel in diesel engines is expressed by the cetane number. In this study, the cetane number was determined using an empirical correlation between density and distillation temperature using the Calculated Cetane Index (CCI) ASTM D 4737 standard. Cutting the boiling point of refinery diesel is carried out to determine its effect on the Calculated Cetane Index (CCI) value. Cutting the boiling point route is done by cutting distillation into 3 variations. The Calculated Cetane Index is measured by calculating the density data of ASTM D 4052 and ASTM D 86 distillation. Solar Feed, which initially had a CCI value of 46, was cut by its heavy fraction in stages to variation 2, the value decreased to 41.6. In variation 3, the light fraction was cut in stages, the result showed that the CCI value increased to 55.2. The results of the Fourier Transform Infrared Spectroscopy (FTIR) characterization showed the presence of C-H stretching and C-H bending functional groups at wave numbers 2900 cm-1 and 1456 cm-1 The higher the hexadecane composition, the higher the CCI value. The results of the analysis using the Gas Chromatography-Mass Spectrometry (GC-MS) instrument proved that Solar 3.4 has the highest hexadecane composition of 10.19%. Solar Feed has a hexadecane composition of 6.45% while Solar 2.4 has the lowest hexadecane composition of 4.56%. Keywords: Diesel Fuel, Cetane Number, Calculated Cetane Index, Distillation